Émigration, résistance et démocratisation - Victor Pereira (Mélanges de la Casa de Velázquez, 2007)
While some authors consider that the departure for Europe of almost one million four hundred thousand Portuguese between 1960 and 1974 encouraged the emergence of democracy in Portugal, it is nonetheless the case that migrants are almost always depicted as non-actors of History. This view stems from a negative interpretation of emigration, which sees it as favourable to the authoritarian Portuguese regime. This analysis, then, fails to identify such movement as one of the means of protest developed by the Portuguese lower classes. This article seeks to qualify these analyses and put emigration in its proper place among the forms of protest available to the lower classes under the dictatorship. It also seeks to show how this movement sponsored the circulation of ideas and ways of seeing things, and how it provoked feelings of dissatisfaction which prepared the ground for the emergence, and above all, the consolidation of democracy.